Inventarios de insectos asociados con arvenses en plantaciones de Tectona grandis L. f. (teca) con control químico, mecánico y sin control, en los sectores: La palma del cantón Buena Fe y Yurac Yacu del Cantón Valencia, Provincia de Los Ríos, año 2019. - Moscoso Manjarres, Marjorie Mabel (2019)
The objective of this research was to determine the diversity and abundance of insect species associated with weeds in teak plantations with chemical, mechanical and uncontrolled control, in the following sectors: La Palma, canton Buena Fe and Yurac Yacu, canton of Valencia, province of Los Ríos, year 2019. 12 traps were installed at ground level, the traps were installed in the center of the sampling units in which a trap was installed for each sampling unit, that is, a total of three traps per site, the traps were used without attractants, the collection of the specimens was done once a week for a month. The samples were collected in containers with a concentration of 70% alcohol and 30% distilled water, identification was carried out by means of dichotomous keys. In total, 33 species were collected with a total of 591 individuals, with La Palma 2011 being the site with the greatest diversity with a value of 0.76 according to Simpson and an average value of 1.92 according to Shannon, the site with the lowest diversity was Yurac Yacu 2011 with an average diversity of 0.67 according to Simpson and an average diversity according to Shannon 1,61. The treatment with greater diversity was the chemical control with 0.863 (Simpson) and 2.24 (Shannon). The site with the highest abundance was La Palma 2009 with 244 individuals and the one with the lowest abundance was Yurac Yacu (2011-2009) with 81 individuals each site, in the treatments; the one that had the largest number of individuals was the uncontrolled treatment with 337 and the one with less abundance was the treatment with chemical control with 81 individuals. Keywords: Diversity, insects, abundance, traps